Determinants of Employee Retention : The Roles of Career Development, Engagement, and Organizational Culture - Tiara, Tiara; Heriyanti, Sinta Sundari (Talent: Journal of Economics and Business, 2025)
This study aims to determine the extent to which Career Development Strategy, Employee Engagement, and Organizational Culture influence Employee Retention at PT. Cipta Mandiri Wirasakti, while also highlighting the study’s theoretical relevance in explaining how human resource practices reinforce employee commitment within the framework of social exchange dynamics. Using a descriptive quantitative method and a sample of 80 employees, the data were analyzed with SPSS 26. This methodological approach not only provides statistical evidence but also strengthens the practical applicability of the findings for HR decision-making in manufacturing settings. The results revealed that all three variables have a positive and significant effect on employee retention: Career Development Strategy, Employee Engagement, and Organizational Culture. Beyond statistical confirmation, these results contribute to existing literature by demonstrating that the integration of development opportunities, psychological engagement, and cultural alignment forms a synergistic retention mechanism in industrial workplaces. These findings indicate that a strong combination of clear career growth opportunities, active employee involvement, and a positive organizational culture contributes significantly to retaining employees. When employees feel valued, engaged, and supported in a growth-oriented work environment, their commitment to the company increases, leading to longer tenure and reduced turnover, thereby offering practical insights for organizations seeking evidence-based strategies to minimize attrition and strengthen workforce stability.